2017
DOI: 10.19044/esj.2017.v13n23p329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media on Self-Esteem

Abstract: Social media has gained immense popularity in the last decade and its power has left certain long-lasting effects on people. The upward comparisons made using social networking sites have caused people to have lower self-esteems. In order to test the hypothesis 150 students from institute of business management were surveyed through questionnaires and interviews. This research was limited to the students of IoBM and Facebook, being the most popular social networking site was used as the representative of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 20 publications
7
67
0
8
Order By: Relevance
“…Mehdizadeh (2007) reported that university students with low levels of self-esteem were involved in more online activities via SNSs. Another related study demonstrated that an increasing use of social media could lead to a decrease in university students' self-esteem (Jan, Soomro, & Ahmad, 2017). In the present study, it was found that negative valence had a relationship with most of the SNS use purposes.…”
Section: Discussionsupporting
confidence: 56%
“…Mehdizadeh (2007) reported that university students with low levels of self-esteem were involved in more online activities via SNSs. Another related study demonstrated that an increasing use of social media could lead to a decrease in university students' self-esteem (Jan, Soomro, & Ahmad, 2017). In the present study, it was found that negative valence had a relationship with most of the SNS use purposes.…”
Section: Discussionsupporting
confidence: 56%
“…Psychologists are increasingly concerned that technology is breaking down family communication. Distracted parents or partners who compare their significant others and life in general to the digital lives of other friends/connections on social media might has impacted their self-esteem (Muqaddas et al, 2017) and family relationship in a negative way (Frampton & Fox, 2018;Carter, 2015). It was stated that partners who cheated on their partner often reported that their own infidelity had been facilitated by social media sites (Carter, 2015;Abbasi & AlGhamadi, 2017).…”
Section: Internet and Social Mediamentioning
confidence: 99%
“…A research conducted by Jan, Soomro, and Nawaz [6] shows that social media has a strong relationship with selfesteem. This finding is supported by Smith-Duff [7] that states social media has a big impact on people's lives since they use this media to enhance their self-esteem levels.…”
Section: Social Media and Self-esteemmentioning
confidence: 99%